Contrast Enhancement Patterns in Pediatric Glioblastomas. Issue 1 (7th September 2022) - Pokhylevych, Halyna; Khose, Swapnil; Gule-Monroe, Maria K.; Chen, Melissa M.; Fuller, Greg; Gruschkus, Stephen K.; Sadighi, Zsila; Zaky, Wafik; Sandberg, David I.; McGovern, Susan L.; Johnson, Jason M.
Abstract : Background and Purpose: Brain tumors are the most common cause of cancer-related deaths among the pediatric population. Among these, pediatric glioblastomas (GBMs) comprise 2.9% of all central nervous system tumors and have a poor prognosis. The purpose of this study is to determine whether the imaging findings can be a prognostic factor for survival in children with GBMs. Materials and Methods: The imaging studies and clinical data from 64 pediatric patients with pathology-proven GBMs were evaluated. Contrast enhancement patterns were classified into focal, ring-like, and diffuse, based on preoperative postcontrast T1-weighted magnetic resonance images. We used the Kaplan-Meier method and Cox proportional hazard regression to evaluate the prognostic value of imaging findings. Results: Patients with ring-enhanced GBMs who underwent gross total resection or subtotal resection were found to have a significantly shorter progression-free survival ( P = 0.03) comparing with other enhancing and nonenhancing glioblastomas. Conclusions: In this study, we analyzed survival factors in children with pediatric glioblastomas. In the group of patients who underwent gross total resection or subtotal resection, those patients with focal-enhanced GBMs had significantly longer progression-free survival ( P = 0.03) than did those with other types of enhancing GBMs (diffuse and ring-like).